Microbial bioindicators associated with cadmium uptake in sixteen genotypes of Theobroma cacao - Jennifer E. Schmidt; Caleb A. Lewis; Alana J. Firl; Pathmanathan Umaharan (Heliyon)
Recent regulatory limits on concentrations of cadmium (Cd), an element of concern for human health, have made Cd reduction a key issue in the global chocolate industry. Research into Cd minimization has investigated soil management, cacao genetic variation, and postharvest processing, but has overlooked the cacao-associated microbiome despite promising evidence in other crops that root-associated microorganisms could help reduce Cd uptake.A novel approach combining both amplicon and metagenomic sequencing identified microbial bioindicators associated with leaf and stem Cd accumulation in sixteen field-grown genotypes of Theobroma cacao. Sequencing highlighted over 200 amplicon sequence variants (ASVs) whose relative abundance was related to cacao leaf and stem Cd content or concentration. The two highest-accumulating genotypes, PA 32 and TRD 94, showed enrichment of four ASVs belonging to the genus Haliangium, the family Gemmataceae, and the order Polyporales. ASVs whose relative abundance was most negatively associated with plant Cd were identified as Paenibacillus sp. (β = −2.21), Candidatus Koribacter (β = −2.17), and Candidatus Solibacter (β = −2.03) for prokaryotes, and Eurotiomycetes (β = −4.58) and two unidentified ASVs (β = −4.32, β = −3.43) for fungi. Only two ASVs were associated with both leaf and stem Cd, both belonging to the Ktedonobacterales. Of 5543 C d-associated gene families, 478 could be assigned to GO terms, including 68 genes related to binding and transport of divalent heavy metals. Screening for Cd-related bioindicators prior to planting or developing microbial bioamendments could complement existing strategies to minimize the presence of Cd in the global cacao supply.